2017
DOI: 10.1007/s00204-017-2144-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials: certain aspects of application, risk assessment and risk communication

Abstract: Development and market introduction of new nanomaterials trigger the need for an adequate risk assessment of such products alongside suitable risk communication measures. Current application of classical and new nanomaterials is analyzed in context of regulatory requirements and standardization for chemicals, food and consumer products. The challenges of nanomaterial characterization as the main bottleneck of risk assessment and regulation are presented. In some areas, e.g., quantification of nanomaterials wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 143 publications
0
65
0
3
Order By: Relevance
“…Securing the right dosage, the proper way of application, the adequate exposure time, and the parameters that affect the performance of the nanomaterials in different media (e.g., size, agglomeration, mobility, precipitation, etc.) are key factors that might compromise the validity of results …”
Section: Toxicity and Environmental Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Securing the right dosage, the proper way of application, the adequate exposure time, and the parameters that affect the performance of the nanomaterials in different media (e.g., size, agglomeration, mobility, precipitation, etc.) are key factors that might compromise the validity of results …”
Section: Toxicity and Environmental Impactmentioning
confidence: 99%
“…are key factors that might compromise the validity of results. 96 In general terms, an ideal nanodevice for use in agricultural should comprise the following traits: (i) it should be non-toxic and environmentally safe, to avoid further contamination problems and a negative perception on the part of consumers; (ii) its synthesis and production must be easily up-scaled; (iii) it should involve low-cost materials, so that the cost of the new nanoformulated products does not exceed that of the current agrochemicals and they are affordable to farmers. 97 In order to clarify the needs and achieve conformity among procedures, the EFSA has very recently prepared a guidance statement concerning risk assessment of nanoscience, nanoobjects and nanotechnology applications in the food and feed chain for humans and animals.…”
Section: Toxicity and Environmental Impactmentioning
confidence: 99%
“…Taking advantage of their small size, nanomaterials are hypothesized to penetrate cellular membranes, biological barriers and tissues more efficiently than larger sized materials (Gidwani and Singh 2013). However, a large number of biokinetic studies has only revealed a minor influence of particle size on biodistribution (Laux et al 2017b). The field of nanotoxicology is concerned with classifying the conditions that lead to toxic effects and devising ways to prevent and treat them.…”
Section: Introductionmentioning
confidence: 99%
“…In this review article, we revisit a nanosafety conclusion from an emerging trend of a decade of nanotoxicity research. Since the inception of nanotechnology more than three decades ago, there has been a concern that the term 'nano' was somehow inherently related to dangerous (Laux et al 2017b). This was majorly propagated by a media hype, science fiction and books seeking attention of public with the term 'nano' which introduced imaginary self-replicating nanobots (Joachim 2005;McCray 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation